2016
DOI: 10.1121/1.4971880
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior of a frequency-domain nonlinearity indicator for solutions to the generalized Burgers equation

Abstract: A frequency-domain nonlinearity indicator has previously been characterized for two analytical solutions to the generalized Burgers equation (GBE) [Reichman, Gee, Neilsen, and Miller, J. Acoust. Soc. Am. 139, 2505–2513 (2016)], including an analytical, asymptotic expression for the Blackstock Bridging Function. This letter gives similar old-age analytical expressions of the indicator for the Mendousse solution and a computational solution to the GBE with spherical spreading. The indicator can be used to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Furthermore, since higher pressures gives rise to greater phase speeds (Hamilton & Blackstock, ), we expect a positive correlation between maximum signal pressure and maximum νNtot and a negative correlation between maximum signal pressure and minimum νNtot. These relationships have been qualitatively observed in applications to computationally propagated waves (Reichman et al, ; Miller et al, ) and model‐scale jet noise (Miller & Gee, ), as shown in Figure c. This study is the first to extract quantitative metrics from νN.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, since higher pressures gives rise to greater phase speeds (Hamilton & Blackstock, ), we expect a positive correlation between maximum signal pressure and maximum νNtot and a negative correlation between maximum signal pressure and minimum νNtot. These relationships have been qualitatively observed in applications to computationally propagated waves (Reichman et al, ; Miller et al, ) and model‐scale jet noise (Miller & Gee, ), as shown in Figure c. This study is the first to extract quantitative metrics from νN.…”
Section: Methodssupporting
confidence: 59%
“…Various approaches have been used to investigate nonlinear propagation effects such as the statistics of the waveform (e.g., skewness) and its derivative (Anderson et al, ; Fee et al, ; Gee et al, , ), bicoherence (Gee et al, ; ; Kim & Powers, ), and quadspectral density (Gee et al, ; Miller et al, ; Miller & Gee, ; Morfey & Howell, ; Petitjean et al, ; Reichman et al, ). The quadspectral density refers here to the imaginary part of the cross spectrum of pressure and squared pressure ( Qpp2).…”
Section: Introductionmentioning
confidence: 99%